Strategi pemasaran dan penanganan pembiayaan BSI KUR bermasalah studi kasus di Bank BSI Cabang Yogyakarta Kusumanegara - Rahayu, Nur Ellyanawati Esty (Nur Science Institute, 2025)
This research aims to explain the marketing strategy and handling of problematic BSI KUR at Bank BSI Yogyakarta Kusumanegara Branch. The approach researchers use is descriptive-qualitative through primary and secondary data sources. The research period is from 2021-2023. The research sample is Bank BSI Yogyakarta Kusumanegara Branch because it is a branch in Region 07 that has the best growth of BSI KUR and can overcome problematic financing. Data collection methods include interviews with the Branch Manager and Financing Supervisors and direct observation of several activities related to the study subject. This study uses the Miles and Huberman data analysis method, which consists of data reduction, data presentation, conclusion drawing, and verification. The study results explain that the BSI KUR marketing strategy is carried out by implementing the 7P marketing mix, which includes Product, Price, Promotion, Place, People, Process, and Physical Evidence. Meanwhile, handling problematic BSI KUR financing is carried out by ensuring the process of providing BSI KUR financing must be by procedures, 6C and 7P financing analysis, Debtor maintenance and personal approach, and Assistance and settlement of problematic BSI KUR financing.